Efeito da porosidade do substrato casca de pínus no desenvolvimento de mudas de grumixameira - Suguino, Eduardo; Martins, Adriana Novais; Minami, Keigo; Narita, Nobuyoshi; Perdona, Marcos Jose [UNESP] (Soc Brasileira Fruticultura, 2011)
Aiming to evaluate the effect of the pine bark substrate porosity on the development of the grumixama plant (Eugenia brasiliensis Lam.), an experiment was conducted in a greenhouse of the Escola Superior de Agricultura "Luiz de Queiroz"/USP, Piracicaba, Brazil. The treatments were: 100% ground pine bark without separation of particles; 100% pine bark of <= 0,1mm; 75% pine bark of <= 0,1mm + 25% between 0,1-4,0 mm; 50% of pine bark <= 0,1mm + 50% between 0,1-4,0 mm; 25% pine bark of <= 0,1mm + 75% between 0,1-4,0 mm and 100% pine bark of 0,1-4,0 mm. The evaluations (stem diameter, length and average dry weight of seedlings) were performed on the 90, 120 and 150(th) days after sowing. The low water absorption in the early stages and the low aeration of the roots promoted by the substrate, affect the development of the grumixama plant seedlings, that grow best when the total pore space of the substrate is less than 90% (v / v).
Effect of pinus bark substrate porosity in the development of grumixama plant seedlings
Keywords: seedling production; porous space; Eugenia brasiliensis; grumixama; native plants